2007
DOI: 10.1093/geronb/62.5.p239
|View full text |Cite
|
Sign up to set email alerts
|

Age-Related Differences in Control Processes in Verbal and Visuospatial Working Memory: Storage, Transformation, Supervision, and Coordination

Abstract: We explored age differences in transformation, supervision, and coordination processes in verbal and visuospatial repetition-detection tasks. Older adults processed information more slowly and less accurately than did younger adults, especially in the visuospatial task. However, there were no process-specific age-related differences in the visuospatial domain. In the verbal domain, task conditions requiring supervision and coordination showed larger age effects than the baseline or transformation conditions. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
49
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(53 citation statements)
references
References 28 publications
3
49
1
Order By: Relevance
“…The results showed a significant interaction of 300 700 Lag (ms) older, dual task older, single task young, dual task young, single task p < .001). The results thus suggest that the MT differences between young and older adults at Lags 1 and 3 were not simply due to general slowing (see also Bopp & Verhaeghen, 2007;Faust, Balota, Spieler, & Ferraro, 1999).…”
Section: General Slowing Vs Specific Attentional Blink Effectmentioning
confidence: 74%
“…The results showed a significant interaction of 300 700 Lag (ms) older, dual task older, single task young, dual task young, single task p < .001). The results thus suggest that the MT differences between young and older adults at Lags 1 and 3 were not simply due to general slowing (see also Bopp & Verhaeghen, 2007;Faust, Balota, Spieler, & Ferraro, 1999).…”
Section: General Slowing Vs Specific Attentional Blink Effectmentioning
confidence: 74%
“…After this initial working memory decline, discrimination in tasks from the visuospatial domain displayed a more pronounced decay with advancing age tan those from the verbal domain. Some previous studies have observed performance differences between domains in both sexes (e.g., Bopp and Verhaeghen 2007;Fiore et al 2012;Myerson et al 1999), while others have not (Park et al 2002;Borella et al 2008). Importantly, this uneven decline between domains was observed only when the number of years of education was introduced as a covariant to control for its possible effects on the dependent variables.…”
Section: Domainmentioning
confidence: 82%
“…Although some authors (Park et al 2002;Borella et al 2008) observed that the working memory for both types of material decreased equally across the adult lifespan, results have been controversial in studies that have compared age groups at both extremes. Age-related effects were observed to be greater for visuospatial than for verbal working memory in some studies (e.g., Bopp and Verhaeghen 2007;Fiore et al 2012;Myerson et al 1999), but the opposite was found in another study (Vecchi et al 2005). These contradictory results may be due to the difficulty in equating the tasks for both domains, especially when diverse processing demands are also required, such as in span tasks.…”
Section: Introductionmentioning
confidence: 93%
“…Visual working memory is more strongly correlated with general fluid intelligence, whereas verbal working memory is more strongly associated with crystallized intelligence (Bergman & Almkvist, 2013;Dang, Braeken, Ferrer, & Liu, 2012;Haavisto, & Lehto, 2005; though see Colom, Flores-Mendoza, & Rebollo, 2003;Conway, Cowan, Bunting, Therriault, & Minkoff, 2002;Verguts & De Boeck, 2001), possibly reflecting increased executive demands of common visuospatial working memory tasks (e.g., Vandierendonck, Kemps, Fastame, & Szmalec, 2004). In line with this, research has demonstrated that visuospatial working memory is particularly agesensitive, compared to the verbal component of working memory (Bo, Jennett, Seidler, 2012;Hale et al, 2011;Park et al, 2002;Jenkins, Myerson, Joerding, & Hale, 2000;Jenkins, Myerson, Hale, & Fry, 1999;Verhaeghen, Cerella, Semenec, Leo, Bopp, & Steitz, 2002;Bopp & Verhaeghen, 2007). Thus, separable subcomponents may have different age-related trajectories (Dang et al, 2012).…”
Section: Working Memory In Agingmentioning
confidence: 86%